Nghiên cứu khả năng tách loại, thu hồi một số kim loại nặng trong dung dịch nước bằng vật liệu hấp phụ sinh học được chế tạo từ rong tảo biển - Nội, Nguyễn Văn; Thu Hiền, Chu Thị (Vietnam Journal of Chemistry, 2014)
Gracilaria used as a sorbent was cross-linked with glutaraldehit. The equilibrium sorption uptake of two metal ions (Cr3+, Ni2+) on the sorbent was investigated by using Langmuir sorption model during the batch contact process. The maximum uptake (qmax) was 0.16 mmol/g (8.40 mg/g) and 0.14 mmol/g (8.46 mg/g) for chromium and nickel, respectively. Beside this, the removal of those metals from aqueous solution at pH = 4.0 was investigated under regime of continuous flow sorption process. For desorption and assessment of the amount of adsorbed metals, the solution of sulfuric acid was used. Of course, the sorbent regeneration was investigated via reuse of the sorbent again